Heterogeneous Catalysts for Glycerol Biorefineries: Hydrogenolysis to 1,2-Propylene Glycol - Gatti, Martin Nicolas (2023)
Research on the use of biomass resources for the generation of energy and chemical compounds is of great interest worldwide. The development and growth of the biodiesel industry has led to a parallel market for the supply of glycerol, its main by-product. Its wide availability and relatively low cost as a raw material make glycerol a basic component for obtaining various chemical products and allows for the development of a biorefinery around biodiesel plants, through the technological integration of different production processes. This work proposes a review of one of the reactions of interest in the biorefinery environment: the hydrogenolysis of glycerol to 1,2-propylene glycol. The article reviews more than 300 references, covering literature from about 20 years, focusing on the heterogeneous catalysts used for the production of glycol. In this sense, from about 175 catalysts, between bulk and supported ones, were revised and discussed critically, based on noble metals, such as Ru, Pt, Pd, and non-noble metals as Cu, Ni, Co, both in liquid (2?10 MPa, 120?260 °C) and vapor phase (0.1 MPa, 200?300 °C). Then, the effect of the main operational and decision variables, such as temperature, pressure, catalyst/glycerol mass ratio, space velocity, and H2 flow, are discussed, depending on the reactors employed. Finally, the formulation of several kinetic models and stability studies are presented, discussing the main deactivation mechanisms of the catalytic systems such as coking, leaching, and sintering, and the presence of impurities in the glycerol feed. It is expected that this work will serve as a tool for the development of more efficient catalytic materials and processes towards the future projection of glycerol biorefineries.